2017
DOI: 10.1515/afmnai-2017-0008
|View full text |Cite
|
Sign up to set email alerts
|

The Relation between Academic Achievement and Emotional Intelligence in Iranian Students: A Meta-Analysis

Abstract: SU M M A RYAcademic achievement is one of the most important concepts in the field of education. Although emotional intelligence, as a key factor in academic achievement, has been studied in various studies, yet the results obtained are not in harmony with each other and the topic is yet under debate. In order to fill in this informational vacuum, the present research was undergone using a meta-analysis method.In order to make a thorough search to find articles within the Iranian context, key words such as "Em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 19 publications
2
13
0
1
Order By: Relevance
“…The outcomes of the study are also supported by the findings of Fallahzadeh [8] who affirmed a considerable association between emotional intelligence and academic performance although findings showed a significant association between two subdimensions of emotional intelligence and academic performance. Ranjbar, Khademi, and Areshtanab [49] found a weak correlation between educational success and emotional intelligence. They noted that the association of these variables may be influenced by other variables in this setting, so it needs further investigation in this area.…”
Section: Discussionmentioning
confidence: 99%
“…The outcomes of the study are also supported by the findings of Fallahzadeh [8] who affirmed a considerable association between emotional intelligence and academic performance although findings showed a significant association between two subdimensions of emotional intelligence and academic performance. Ranjbar, Khademi, and Areshtanab [49] found a weak correlation between educational success and emotional intelligence. They noted that the association of these variables may be influenced by other variables in this setting, so it needs further investigation in this area.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Kashani et al (2012) examined the association between EI and educational achievement in a correlation study using 100 university students from Tehran and found no association between the two constructs. Also, Ranjbar et al (2017) reviewed all published studies that investigated the correlation between EI and academic achievement among Iranian students. There were a total of 23 articles that were used for the meta‐analysis using the comprehensive meta‐analysis software (version 3).…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Also, Ranjbar et al (2017) reviewed all published studies that investigated the correlation between EI and academic achievement among Iranian students. There were a total of 23 articles that were used for the meta-analysis using the comprehensive meta-analysis software (version 3).…”
Section: Introductionmentioning
confidence: 99%
“…Igualmente, se ha encontrado que la IE se asocia positivamente y tiene capacidad predictiva sobre el rendimiento académico del alumnado universitario (Perera y DiGiacomo, 2013Ranjbar, Khademi, y Areshtanab, 2017;Sánchez-Ruiz, Mavroveli, y Poullis, 2013). Entre las habilidades de la IE, en una investigación destacan la regulación y la percepción emocional (Lanciano y Curci, 2014) y en otros estudios sobresale la regulación de las emociones como la que mayor relación y capacidad predictiva presenta sobre el rendimiento académico del alumnado (Antonio-Agirre, MacCann, Fogarty, Zeidner, y Roberts, 2011).…”
unclassified